In the Service of His Korean Majesty : William Nelson Lovatt, the Pusan Customs, and Sino-Korean Relations, 1876-1888 - Patterson, Wayne, 1946- (Book collections on Project MUSE., 2012)
"This book, based upon the correspondence of William Nelson Lovatt, Korea's first commissioner of customs in Pusan, looks at the informal imperialism exercised by China over Korea in the 1880s, as China's increasing interventionism affected Lovatt's hiring, his experiences in Korea, and his eventual termination"--Provided by publisher.